Reusing Parchment as Writing Support in Pre-modern Iceland: The Cases of Two Jónsbók Palimpsests from the Sixteenth and Seventeenth Centuries - Lejia Zhang 2000- (2024)
This thesis studies the practice of reusing parchment as writing support in pre-modern Icelandic book production. Published scholarship on Icelandic palimpsests largely concentrates on individual manuscripts, whereas comprehensive research on the socio-cultural implications of this phenomenon remains absent. This thesis contributes to a quantitative overview of known Icelandic palimpsests, investigating when palimpsest making occurred, what manuscripts were recycled, and for what manuscripts recycled parchment was employed. The case studies on AM 38 8vo and NKS 1931 4to, two Jónsbók palimpsests from the sixteenth and seventeenth centuries, explore how recycled parchment was appropriated for the new manuscripts through structural codicological analyses. Contextualising the Jónsbók palimpsests into their production background and use history, the last chapter infers the possible reasons why recycled parchment was preferred for these manuscripts. The quantitative survey reveals that a) most extant Icelandic palimpsests were produced in the sixteenth and seventeenth centuries; b) Latin liturgical manuscripts were most frequently reused as writing support, especially after the Reformation; and c) Jónsbók seems to be most commonly found as the overtext of the Icelandic palimpsests. The case studies demonstrate that how and why recycled parchment was employed seem to vary for different Jónsbók manuscripts. For the largely practical AM 38 8vo, the reuse seems to be casual and utilitarian, possibly motivated by expenditure and durability requirements. For NKS 1931 4to, the scribe appropriated recycled parchment in a thoughtful and purposeful manner, probably driven by aesthetic considerations to elevate the book’s prestige with limited resources. This thesis also contains a catalogue of sixty-six Icelandic palimpsests. Þessi ritgerð fjallar um endurnýtingu bókfells til að skrifa á íslenskri fornútímalegri bókagerð. Útgefin fræðirit um íslenska uppskafninga beinist að mestu leyti að einstökum handritum en stærri ...